(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we develop an iterative method of lines scheme for the numerical solution to the time fractional Richards equation with implicit Neumann boundary conditions, which is an effective tool for describing a process of flow through unsaturated media. A numerical example is provided to show the effectiveness of the presented method for different model parameters and inputs. The method illustrated here can be applied to other types Richards equation with various input functions and Dirichlet boundary conditions.